Analisis Faktor-Faktor yang Mempengaruhi Profitabilitas Bank Perekonomian Rakyat Konvensional di Provinsi Riau dengan Intellectual Capital sebagai Faktor Pemoderasi - Afandi, Ahmad; Kamalia, Kamalia; Rokhmawati, Andewi (Jurnal Manajemen dan Inovasi (MANOVA), 2024)
This research aims to test and analyze the influence of NPL, LDR, BOPO and CAR on Profitability with Intellectual Capital as a Moderating Variable. The population and sample used were 27 Conventional People's Economic Banks in Riau Province. The analytical method used is MRA analysis (Moderate Regression Analysis). The research results show that there is an influence of BOPO on profitability. Meanwhile, NPL, LDR and CAR have no effect on profitability. Meanwhile, Intellectual Capital has not been able to be a moderating factor between NPL, LDR and CAR on profitability, but Intellectual Capital has been able to moderate the influence of BOPO on profitability.